Intestinal Permeability Assays: a Review - Iakupova, A. A.; Abdulkhakov, S. R.; Zalyalov, R. K.; Safin, A. G.; Abdulkhakov, R. A. (Rossiĭskiĭ zhurnal gastroėnterologii, gepatologii, koloproktologii, 2021)
Aim . A literature review of intestinal permeability assessment techniques. Key points . The intestinal barrier is a functional entity separating the intestinal lumen and internal body, and intestinal permeability is a measure of the barrier functionality. The intestinal barrier integrity and permeability assays differ by the application setting ( in vivo or ex vivo ), subject (human or animal), marker molecules used to assess permeability (ions, various size carbohydrates, macromolecules, antigens, bacterial products and bacteria), biomaterial for the marker concentration assays (peripheral blood, portal venous blood, urine, stool). Despite a great variety of methods for assessing intestinal permeability, their clinical application requires further studies due to a lack of standardisation, the complexity of selected techniques and occasional limited reliability of results. Conclusion . Further investigation and improvement of intestinal permeability assays is required. The assay and result standardisation will facilitate practice in functional and organic intestinal diseases, as well as allergies, diabetes mellitus, non-alcoholic fatty liver disease and some other illnesses.